Fabrication and Electrical Characterization of ISFET for H2O2sensing - Duarte, Pedro H.; Rangel, Ricardo C.; Ramos, Daniel A.; Yojo, Leonardo S.; Mori, Carlos A.B.; Sasaki, Katia R. A. [UNESP]; Agopian, Paula G. D. [UNESP]; Martino, Joao A. (Institute of Electrical and Electronics Engineers (IEEE), 2022)
This work presents the fabrication and electrical characterization of the Ion-Sensitive Field Effect Transistor (ISFET) exposed to hydrogen peroxide solutions. Two configurations were set up to evaluate the sensitivity of the devices to the concentration of the solution. First, measurements with one electrode in the sample solution (contained over the gate area) were performed; however, due to the prevalence of secondary effects, the results may not be directly related to the characteristics of the solution. The second method, using two electrodes in the sample solution, shows a higher sensitivity at increasing H2O2 concentrations, and in decreasing intervals, when compared to measurements with one electrode.
Keywords: Biosensor; Hydrogen Peroxide sensing; ISFET